Pengaruh Literasi Keuangan dan Pengetahuan Investasi terhadap Minat Investasi dengan Perilaku Keuangan Sebagai Variabel Intervening pada Gen Z di Kota Bengkulu. - Estu Maha Nanik; Idham Lakoni; Sintia Safrianti (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to determine whether financial literacy and investment knowledge have a direct influence on investment interest, and to determine the effect of financial literacy and investment knowledge on investment interest through mediation of financial behavior. The research approach used in this research is associative. The type of data used in this research is quantitative data and the data source using primary data, namely research data obtained directly from the original source (respondents). The population in this study is generation Z in Bengkulu City. From the calculation using the formula (Hair et al, 2014) with a total of 150 respondents. This research data was processed using the smartPLS version 4 analysis tool and Smart-PLS is an alternative method of SEM analysis using partial least squares or partical last square (PLS). Dirrect Effect research results conclude that the first hypothesis of financial literacy affects investment interest, the second hypothesis of investment knowledge has a significant positive effect on investment interest, the third hypothesis of financial literacy has a significant positive effect on financial behavior, the fourth hypothesis is not supported because investment knowledge has no significant effect on financial behavior, the fifth hypothesis is not supported because investment interest has no significant effect on financial behavior. The research results of the indirect effect resulted in the sixth hypothesis not supported because, financial literacy directly has no effect on investment interest through financial behavior as an intervening variable, the seventh hypothesis is not supported because, investment knowledge directly has no effect on investment interest through financial behavior as an intervening variable.